Enhancing students' problem solving skills using problem-based learning as an instructional communication approach - Abdul Kadir, Zulida (2013)
Malaysian graduates do not fulfill the criteria as good potential workers as they are not efficient at the workplace and lacking of soft skills. One of the reasons why our graduates are not fulfilling the industry needs is due to low problem solving skills, which is one of the important aspects of soft skills (Bernama, 2010). To address this issue, the Ministry of Higher Education has proposed several instructional approaches to be used in class, and one of them is problem-based learning (PBL). This study was designed to examine the application of Problem-based Learning as an instructional communication in class, which is believed can help students in enhancing their problem solving skills. A quasi-experimental study was done in investigating the effectiveness of problem-based learning (PBL) as an instructional approach. Two groups of students were selected as the subjects of this research: the PBL group and non-PBL group. Subjects were assessed on their problem solving skills at the beginning and at the end of the semester. For the PBL group, their perceptions towards PBL environment and their intrinsic motivation were measured before and after receiving the PBL treatments. In measuring the problem solving skills and solutions on PBL treatments, two inter-raters were employed in assessing them from the aspects of “accuracy” and “quality”. The “accuracy” and “quality” were measured using rubric used in Malaysian University English Test (MUET) examination. Selected questions from Motivated Strategies for Learning Questionnaire by Pintrich and DeGroot (1990) and Problem-based Learning Environment by Senocak (2009) were used in measuring students’ intrinsic motivation and their perception towards PBL environment. Furthermore, in examining PBL efficacy, this study used Social Development Theory by Vygotsky and The Toulmin Model of Argumentation. The findings revealed that there were significant differences on students’ problem solving skills in PBL group compared to non-PBL group. Students in PBL group had better problem solving skills after experiencing four PBL treatments. They also perceived PBL in positive ways in enhancing their problem solving skills. However, their motivation did not change much, thus contributed to insignificant results. Finally, in investigating the relationship among motivation, and perceptions towards learning environment, with problem solving skills, results showed that only motivation associated with problem solving skills. In summary, this study demonstrates that students can enhance their problem solving skills through problem-based learning as one of instructional approaches in class as proposed by Ministry of Higher Education. Using this approach, the findings of this study are able to provide fresh ideas for teaching and learning in undergraduates’ courses by preparing syllabus which integrates the content knowledge and the requirements of industry.